Juridical Analysis of Fiscal Corrections on the Amortization of Game Development Costs: A Case Study of Toge Productions - Helen Setia Budi; Gunardi Lie (Media Hukum Indonesia (MHI), 2026)
This research examines a judicial review of the amortization treatment of intangible assets regarding video game development costs, focusing on a case study of Toge Productions. With the rapid growth of the digital economy, game development costs capitalized as intangible assets often face synchronization issues between commercial useful life and fiscal regulations. The research method employed is normative legal research with a statutory approach and case analysis. The results indicate that under Law Number 7 of 2021 and Minister of Finance Regulation (PMK) Number 72 of 2023, game development costs must be amortized. However, the practice of fiscal correction by tax authorities, which enforces a four-year useful life (Group 1), often contradicts the economic reality of the creative industry, where product lifecycles are shorter (two years). This leads to legal uncertainty and a violation of the ability-to-pay principle for taxpayers. This study suggests the need for more adaptive standardization of digital asset useful lives to support the competitiveness of the national creative industry.